Evaluation of physiotherapeutic duty passage in hospital scope (Research, Society and Development, 2022)
The term shift change refers to the moment when a health team transmits information when changing work shifts, when the patient is identified, as well as the clinical condition of each one of them and the definition of the need for planning and execution of necessary care measures. The objective of the research was to evaluate a form of physical therapy shift change at the University Hospital of the Federal University of Piauí (HU-UFPI). The study was carried out in the Intensive Care Unit (ICU) and in nursing stations. The group of physiotherapists participating in this research consisted of 23 professionals. A form was applied to outline the profile of the sample, followed by a semi-structured interview with 10 professionals for a qualitative analysis of the shift change. care performed by physiotherapists in each sector. When the physical therapy shift change in the evaluated service occurs in person, a minority of professionals use the printed shift change sheet, and a minority verbalize the patient's full name at the time of the change. The professionals reported as negative points such as interference caused by the noise of the sectors and considered the printing of the instrument to be costly, however, they recognized the importance of the moment of shift change for safe and qualified continuity of care, and that the form is an instrument that guarantees the recall of relevant patient information.